Incentives for Management - Planning Commission (Planning Commission,Government of India, 1965)
The discussion draft by the COPP Management Group for the National Planning Council explores the design and implementation of incentive schemes for middle and senior management in public sector enterprises in India. Unlike existing incentive structures for workers and first-line supervisors, managerial incentives remain underdeveloped. The document emphasizes the dual purpose of incentives: motivating management personnel to achieve operational and financial objectives while promoting sustained organizational effectiveness. Drawing lessons from global practices, the report highlights both financial incentives—such as bonus funds, deferred payments, and stock options—and non-financial incentives, including recognition and promotions. Critical elements for successful implementation include clearly defined objectives, comprehensive performance measurement, a supportive organizational structure, and a complementary salary framework. Challenges include the subjective assessment of executive performance, risks of prioritizing short-term profits over long-term sustainability, and the need to tailor incentive plans to specific organizational contexts. The report concludes that well-designed and context-sensitive incentive programs can significantly enhance management performance, foster employee engagement, and contribute to overall organizational success in Indian public enterprises.
Management Group Committee on Plan Projects (Planning Commission), October 1965
Management Group Committee on Plan Projects (Planning Commission), October 1965
Keywords: Management Incentives; Public Sector Enterprises; Performance Motivation; Financial Incentives; Non-Financial Incentives; Bonus Fund; Deferred Payments; Stock Options; Organizational Objectives; Performance Measurement; Executive Evaluation; Operational Efficiency